Analisis Kepuasan Kerja Dan Komitmen Organisasi Terhadap Kinerja Pegawai PNS Dan Non PNS Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Tulungagung - Afifah Nuraini; Imam Baehaki (Universitas Islam Kadiri, 2020)
This study aims to determine the effect of job satisfaction and work commitment on the performance of civil servants and non civil servants and to see differences in job satisfaction and work commitment to the performance of civil servants and non civil servants. This research is an explanatory study with a quantitative approach. This research was conducted at the Public Works and Spatial Planning Office of Tulungagung Regency. The total population is all employees, amounting to 232 people. The sampling technique was purposive sampling as many as 70 people consisting of 35 civil servants and 35 non civil servants. While the descriptive data analysis method, (1) classical assumption test, and (2) inferential statistical analysis which includes multiple regression analysis, simultaneous F test, partial t test and Anova. The results showed that: Job satisfaction and organizational commitment of Civil Servants. and Non-Civil Servants have a significant effect on employee performance. Job satisfaction has a positive and significant effect on the performance of both Civil Servants and Non-Civil Servants. Organizational commitment has a significant effect on the performance of both Civil Servants and Non-Civil Servants. The results of the analysis show that there is a significant difference between the job satisfaction of civil servants and civil servants. For organizational commitment and performance, there is no significant difference in the commitment of Civil Servants and Non-Civil Servants.